2012
DOI: 10.1007/s00216-012-6246-6
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity outcome of silica nanoparticles (Ludox®) is influenced by testing techniques and treatment modalities

Abstract: We analyzed the influence of the kind of cytotoxicity test and its application modality in defining the level of hazard of the in vitro exposures to nanostructures. We assessed the cytotoxicity induced by two different Ludox® silica nanoparticles (NPs), AS30 and SM30, on three human cell lines, CCD-34Lu, A549, and HT-1080. Dynamic light scattering measurements showed particle agglomeration when NPs are diluted in culture medium supplemented with fetal calf serum. We examined the impact of such particle aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…It seems to be very important to compare the toxicity data obtained via different methods in order to explain cell response to nanoparticles exposure (Fede et al 2012). There are many studies, however, concerning the toxicity of silver and silica nanoparticles, but the precise mechanism of interaction between living cells and silica nanoparticles, and the silver-silica nanoparticles system are still not known, requiring further investigations (Kim et al 2015;Fede et al 2012;Rabolli et al 2011;Besinis et al 2014;Schneider 2017).…”
Section: Estimation Of the Antibacterial Activity Of The Fibersmentioning
confidence: 99%
“…It seems to be very important to compare the toxicity data obtained via different methods in order to explain cell response to nanoparticles exposure (Fede et al 2012). There are many studies, however, concerning the toxicity of silver and silica nanoparticles, but the precise mechanism of interaction between living cells and silica nanoparticles, and the silver-silica nanoparticles system are still not known, requiring further investigations (Kim et al 2015;Fede et al 2012;Rabolli et al 2011;Besinis et al 2014;Schneider 2017).…”
Section: Estimation Of the Antibacterial Activity Of The Fibersmentioning
confidence: 99%
“…Nanoparticles, material that has between 1 to 100 nanometer, have shown special toxicity and are usually more toxic than the bulk material of larger size (DONALDSON et al, 2001). SiNP have been studied recently and extensive applications have been found for these particles, it can be used as additives to drugs, chemical industry, printer toners, cosmetics and food (FEDE et al, 2012). Although many studies have shown the cytotoxicity of silica nanoparticles (SiNP) in vitro and in vivo (NAPIERSKA et al, 2009;YE et al, 2010;LU et al, 2011;PASSAGNE et al, 2012;AHMAD et al, 2012) RODRIGUEZ, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous applications for silica nanoparticles (SiNP) and it can be used in many fields: chemical industries, biomarkers in medicine, cosmetics, paints, food and medicine (WEI et al, 2010;FEDE et al, 2012. ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations